PRACTICAL ISSUES OF LEGAL REGULATION OF THE AGE CRITERION DURING THE CONCLUSION OF THE EMPLOYMENT CONTRACT - Дибань, Максим Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to analyze the main theoretical and practical problems of legal regulation of setting the age criterion when hiring, to propose ways of solving problems in the legislation on labor in the regulation of protection of labor rights of employees. Methods: methodological basis of research - a set of general scientific and special methods and techniques of scientific knowledge. The basis of scientific research is structural-functional, logical-semantic, system-structural, comparatively legal and other methods. Results: are argued that the current labor legislation requires reform in terms of determining the minimum age for employment, there is a need to reduce the minimum age for employment in certain areas of activity. After all, reconciling the interests of the parties at the stage of concluding an employment contract is a complex and contradictory process that depends on many factors, such as: the law-abiding and the level of employer conscientiousness, the direction of the employee to protect their rights and legitimate interests in the field of work. It is a mistake to assume that the interests of the employer and the employee are fully aligned, although reaching a consensus on all the terms of the employment contract is the «maxsima» to which the parties must strive. Discussion: the issue of observance of labor legislation on labor in the process of its implementation is considered, in particular at the stage of the emergence of individual labor relations - the conclusion of an employment contract, in many aspects it is the determining factor of democratization and stability of labor relations, as well as the guarantee of honesty, reconciliation. But the lack of an effective legal mechanism to regulate the emergence of employment relationships with respect to safeguards, as a means of securing the rights of the individual, the spread of ejijism as discrimination against the elderly in the labor market, lead to violations labor rights.